Sero Positivity of Hepatitis B & C Markers Among Non-Icteric Children Attending A Tertiary Hospital in Dhaka City - Matin, Abdul; Islam, Md Rafiqul; Roy, Ranjjt Ranjan; Mowla, Md Golam; Alam, ABM Shahidul; Khan, Rita; Islam, Md Reazul (Bangladesh Journal of Child Health, 2012)
Background: Viral hepatitis is a major public health problem both in developing and developed countries. Hepatitis B (HBV) and C (HCV) viruses can cause important morbidity and mortality and are major causes of acute and chronic liver diseases worldwide and often leads to cirrhosis or primary hepatocellular carcinoma. The prevalence of infection varies from country to country and within countries. Aim & objectives: This study was an attempt to evaluate the seroprevalence rate of hepatitis B and C in non-jaundiced children who were admitted at Bangabandhu Sheikh Mujib Medical University. Methods: A total of 100 non-icteric admitted children with different childhood diseases of either sex selected randomly were studied during July 2004 to June 2005 in the Department of Pediatrics and Microbiology, Bangabandhu Sheesikh Mujib Medical University. Venous blood was tested for HBsAg and anti-HBc (IgM) and anti-HCV viral markers by ELISA technique using kits from Dia Sorin S.n.I, Italy. Results: The HBsAg test was positive among 19.0 %, Anti-HBc (IgM) test positive in 11.0 % and Anti-HCV test positive in 2.0 % non-icteric admitted children. Positivity was higher in male children. HBsAg was positive in 68.4% of male children and 31.5% of female children. Sero positivity was more in the 5-9 years age group. Noseroposivity was related to blood and blood products transfusion in cases of hepatitis B infection. Conclusion: As this study shows high rate of HBsAg and Anti-HBc (IgM) seropositivity among non-icteric sick children, so further studies with appropriate design & sample size are to be conducted. DOI: http://dx.doi.org/10.3329/bjch.v36i1.13027 Bangladesh J Child Health 2012; Vol 36 (1): 11-15